4k-6=-16-2

Simple and best practice solution for 4k-6=-16-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4k-6=-16-2 equation:


Simplifying
4k + -6 = -16 + -2

Reorder the terms:
-6 + 4k = -16 + -2

Combine like terms: -16 + -2 = -18
-6 + 4k = -18

Solving
-6 + 4k = -18

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4k = -18 + 6

Combine like terms: -6 + 6 = 0
0 + 4k = -18 + 6
4k = -18 + 6

Combine like terms: -18 + 6 = -12
4k = -12

Divide each side by '4'.
k = -3

Simplifying
k = -3

See similar equations:

| 5r-7pq=4 | | 2a+20.4=a+1.6 | | 14t-5t=18 | | 28x=8x+12-7x | | 4x-9x=5-10x | | 2(x+7)=3(x+6) | | 13x+70=24 | | 200(2)-15=y | | 4x+3x-x-8-6+4=32 | | -4(5x-3)+7x=2x-4 | | 6(f+5)-8=2f | | 19u-18u=5 | | 4y-30=y+8+2y-3 | | 200(1)-15=y | | .9x-4.9=.5 | | 5*3v-8=-10 | | -0.25(q-1)+0.5=0.75 | | 200m-75m+57900=61500-175m | | 9x+5(x-2)=2(x-3) | | X^2-2px+9=0 | | [(x)(x)]-7x=44 | | 36-9x=19+8x | | 6p-7=-5p+12 | | 200(1)+15=y | | 4x-2x+15-10-6=19 | | 5y-3=2y-15 | | 200(0)+15=y | | 6-9x=6x-10x+1 | | C=3(a+2b) | | -14=8+h | | 3x+2x-18+13=35 | | 9(3m+4)-7m=-4 |

Equations solver categories